Economic prospects for cooperation the European Union and Ukraine in the use of blockchain technologies - Babenko, Vitalina; Matsenko, Oleksandr; Voronenko, Viacheslav; Nikolaiev, Stanislav; Kazak, Diana (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article is devoted to the research of the possibilities of cooperation between the European Union (EU) and Ukraine in the use of blockchain technologies. The transition to the blockchain allows to minimise costs and maximise the results of economic activity. The experience of using blockchain technologies by world corporations is analysed. The subject of the research in the article is the potential of economic cooperation between the EU and Ukraine in the field of implementation and use of blockchain technologies. The purpose of the article is to find out the economic prospects of cooperation between the EU and Ukraine in the use of blockchain technologies. Tasks: researching of tendencies of development of blockchain technologies and possible variants of their implantation in activity of the Ukraine’s enterprises, searching for benefits from cooperation between Ukraine and the EU in the field of use of blockchain technologies. General scientific used research methods: analysis – to determine the peculiarities of the use of blockchain technologies in the EU, synthesis – to find opportunities for cooperation between Ukraine and the EU in the use of blockchain technologies. The obtained results: based on the analysis of the dynamics of changes in the field of enterprise technology, problematic aspects are identified and the main advantages of the transition from the traditional management model to blockchain platforms are identified, and the economic benefits of locating mining farms in Ukraine compared to some EU countries are calculated. Conclusions: using of blockchain technologies by modern enterprises gives them a number of competitive advantages, including saving on labor costs, increased information security, reduced costs for quality control of products/services, etc. Blockchain allows to promote more sustainable cooperation between EU and Ukrainian companies not only in trade, but also in industry, finance and energy. By implementing joint blockchain systems with the EU, Ukraine can provide mining with low costs for electricity and wages.